2014
DOI: 10.7860/jcdr/2014/7385.4778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Phases of Menstrual Cycle on Reflection Index, Stiffness index and Pulse wave velocity in Healthy subjects

Abstract: Introduction: Arterial compliance will result in stabilizing the fluctuations in arterial pressure and blood flow. So arterial stiffness can be a good indicator for monitoring the cardiovascular system. Arterial stiffness can be measured using indices like reflection index (RI), stiffness index (SI) and Brachial Finger Pulse Wave Velocity (BFPWV).Objectives: Aim of our study was to evaluate the changes in RI, SI and BFPWV during different phases of the menstrual cycle and to correlate RI with SI in healthy fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…Prior research targeting normal women of childbearing age has found decreased blood pressure in the late follicular phase and decreased vessel stiffness [16, 29, 30]. However, this study found that the pulse waves of the menstrual pain group were the exact opposite of the normal comparison group.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Prior research targeting normal women of childbearing age has found decreased blood pressure in the late follicular phase and decreased vessel stiffness [16, 29, 30]. However, this study found that the pulse waves of the menstrual pain group were the exact opposite of the normal comparison group.…”
Section: Discussioncontrasting
confidence: 65%
“…Research on menstrual pulse characteristics has included studies on the effect of different phases of the menstrual cycle on the reflection index, stiffness index, and pulse wave velocity in healthy subjects [16], the influence of the menstrual cycle on pulse pressure waveforms measured from the radial artery in biphasic healthy women [17], the influence of the menstrual cycle on QT interval dynamics [18], and assessment of cardiovascular autonomic functions and baroreceptor reactivity in women with premenstrual syndrome [19]. Lee et al [20] conducted a study on variation in menstrual pulse waves compared to nonmenstrual pulse waves but were unable to concretely determine their characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Neither Hayward and Kelly (1997) nor London et al (1995) reported which phase of the menstrual cycle data were collected. While data have shown that the menstrual cycle affects aortic arterial stiffness (Madhura & Sandhya, 2014), this may not be true for the AIx and AIx@75 (Papaioannou et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of arterial elasticity in the normal menstrual cycle are inconclusive due to small study groups and different methodologies, showing either no changes (29,30) or increased arterial elasticity in the follicular phase, and decreased elasticity in the luteal phase (31)(32)(33). The only PPG study performed in the normal menstrual cycle confirmed the latter finding (34), while the few studies using applanation tonometry for assessment of vascular elasticity have shown no changes or increased elasticity in the luteal phase (18,35). Researchers have speculated that an absent vasodilatory effect or increased stiffness in the luteal phase are due to increased levels of progesterone, which is a potential vasoconstrictor (25), or activation of the renin-angiotensin-aldosterone-system (RAAS) or other hormones that counteract the estrogen effect (30,32).…”
Section: Discussionmentioning
confidence: 80%